An Algorithm for Delimiting Rural Areas According to Soil Classes - Justyna Wójcik-Leń (Land, 2022)
For many years and all over the world, agricultural production has been observed to slow down on low-quality soils in territories featuring difficult topography and poor spatial structure (land fragmentation, excessive elongation of plots, plots without direct access to public roads, and land scattering). This paper proposes a new, self-designed algorithm for delimiting rural areas that allows the clustering of villages featuring low soil productivity, based on three factors used for determining the overall value of the area of land (Wcag), i.e., the overall area of the village (ha), share of specific type of land in the overall area of the village (%), and mean score for specific soil type (pts.), which allows the villages to be grouped according to classes of land occurring in the examined district. The results of the surveys provide a basis for further detailed studies into efficient management of areas featuring low soil classes during land consolidation works. Further surveys will involve a detailed analysis of the identified clusters of villages to ensure that their potential is used to the optimum extent. As a consequence, these areas will potentially become more competitive and operations conducted there will be beneficial to the local inhabitants and contribute to improving their living standard.